The Role of Social Communication in Supporting Public Policy in The Mental Health Sector - Nursinah, Nursinah (Universitas Negeri Makassar, 2023)
Mental health is a health issue that is gaining increasing global attention, especially in today's digital age. This research aims to understand the role of social communication in supporting public policies in the field of mental health. Excavate the impact of the use of social media on mental health that focuses on Generation Z, as a vulnerable group. The study describes the complexity of the relationship between social media and mental health and proposes a balanced approach to supporting public mental health in this digital age. The research methods used in this study are content analysis methods that allow researchers to study these issues in depth using a qualitative approach. Research results show that social media does not always have a negative impact, but can also have a positive effect. Digital literacy and mental health awareness are considered important tools in protecting yourself from the negative impact of social media. The conclusion is that collaboration between government and social media platforms is an important step in addressing mental health problems. Governments have a major role to play in developing regulations that protect their citizens, while social media platforms have the potential to provide valuable resources and information.